2018
DOI: 10.1080/21645515.2018.1469591
|View full text |Cite
|
Sign up to set email alerts
|

Development of new hepatitis E vaccines

Abstract: Hepatitis E virus (HEV) infection is an emerging zoonotic disease posing a severe threat to public health in the world, especially to pregnant women. Currently, no specific treatments are available for HEV infection. Therefore, it is crucial to develop vaccine to prevent this infection. Although several potential candidate vaccines against HEV have been studied for their immunogenicity and efficacy, only Hecolin® which is developed by Xiamen Innovax Biotech Co., Ltd. and approved by China Food and Drug Adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 203 publications
0
16
0
1
Order By: Relevance
“…Along with Hecolin ® , several HEV candidate vaccines are currently being developed and target ORF2 structural capsid protein that coats viral particles 140‐142 . Initial primate studies have shown antibodies raised against ORF2 complete or truncated proteins protected against infections 143 .…”
Section: Vaccinesmentioning
confidence: 99%
“…Along with Hecolin ® , several HEV candidate vaccines are currently being developed and target ORF2 structural capsid protein that coats viral particles 140‐142 . Initial primate studies have shown antibodies raised against ORF2 complete or truncated proteins protected against infections 143 .…”
Section: Vaccinesmentioning
confidence: 99%
“…Although a vaccine for HEV has been developed, it is still under debate and only licensed in China. Thus, more clinical data are needed to verify whether this vaccine or any vaccines being developed work effectively against the different genotypes [37,38].…”
Section: Viral Infections Of the Liver: Hepatitismentioning
confidence: 99%
“…While more than fourteen HEV vaccine candidates have been studied [37], only three candidates have progressed to clinical trials ( Figure 1B). Aluminium-based adjuvants were used in the formulation of all three vaccine candidates.…”
Section: Hepatitis E Vaccinesmentioning
confidence: 99%